2020
DOI: 10.1097/ee9.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Pyrethroid Pesticide Exposures in Adult Life and Depression in Older Residents of California’s Central Valley

Abstract: Pyrethroid pesticide exposures may be associated with the onset of depression in later life via disruption of dopaminergic, serotonergic, and neurological functioning. We sought to investigate the association between living near agricultural pyrethroid pesticide applications and depression measures in central California, using two waves (PEG 1&2, total N = 1,654) of a case control study of Parkinson’s disease (PD). At enrollment, participants self-reported history of use of depression medications and dates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This is especially the case on the evaporation processes. In light of increasing association of potential health outcomes from agricultural pesticides (e.g., Furlong et al, 2020a , 2020b ; Rull et al, 2006 ; Shelton et al, 2014 ), improved capabilities to monitor pesticide abundance, including field measurements for quantifying baseline and ambient concentrations, especially with resuspension, as well as to calibrate and evaluate dispersion models, are strongly recommended, given the increase in pesticide usage, recent reports on their alarming health outcomes, and potential impact of warming in recent years on volatilization of these spray drifts.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case on the evaporation processes. In light of increasing association of potential health outcomes from agricultural pesticides (e.g., Furlong et al, 2020a , 2020b ; Rull et al, 2006 ; Shelton et al, 2014 ), improved capabilities to monitor pesticide abundance, including field measurements for quantifying baseline and ambient concentrations, especially with resuspension, as well as to calibrate and evaluate dispersion models, are strongly recommended, given the increase in pesticide usage, recent reports on their alarming health outcomes, and potential impact of warming in recent years on volatilization of these spray drifts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates that there are 3 million cases of pesticide poisoning each year and up to 220,000 deaths, primarily in developing countries ( Thundiyil et al, 2008 ). Studies have also shown that pesticide exposure can cause a range of neurological health effects such as memory loss, loss of coordination, reduced speed of response to stimuli, reduced visual ability, altered or uncontrollable mood and general behavior, and reduced motor skills ( Shelton et al, 2014 ; Kori et al, 2018 ; Furlong et al, 2020a , b ; Lucero and Muñoz-Quezada, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that, in general, the cited studies resort to the most diverse scales of mental disorders evaluation, referring mainly to the occurrence of depressive and/or anxiogenic disorders in individuals exposed or not to the different types of pesticides. However, these measurement tools, performed through self-report, may not be as reliable in diagnosing depression and anxiety [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Pyrethroids with low mammalian toxicity are now commonly used for household and post-harvest insect control [88]. However, pyrethroid pesticide exposures may be also associated with disruption of neurological functioning [89][90][91][92]. Neonatal exposure to permethrin can induce a Parkinson-like disease.…”
Section: Pyrethroidmentioning
confidence: 99%